PEMILIHAN BENTUK FUNGSI DENGAN MENGGUNAKAN TRANSFORMASI VARIABEL MENURUT BOX-COX (Studi: Permintaan Pariwisata Indonesia Tahun 1985-1995) - Sarwoko Sarwoko (Journal of Indonesian Economy and Business (JIEB), 1998)
This paper describes the select on of the appropriate functional form using extended Box-Cox transformation model. The model is employed to estimate the functional forms of International Tourism Demand to Indonesia from the five's biggest countries of origin: Malasia, Singapore, Japan, Australia and Taiwan. This study also investigates the determinants of those demand functions. Independent variabels, the countries real income, consumer price index ratio, exchange rate, Infrastructure, Promotion of Tourism and dummy variable, General Election in Indonesia were hypothesized to influence tourist arrival and expenditure.. The result indicate that overall, the variabels examined explained a high percentage of variations in dependent variabels, tourist arrival and tourist expenditure. Most variables were statistically significant with the expected signs. In tourist arrival equitions, the log-linier functional form are slightly better for all countries examined. On the other hand, in the expenditure equitions, the linier functional form are slightly better for all countries examined.